IMPLEMENTATION OF FORWARD INFERENCE REASONING IMPLEMENTING THE DEMPSTER-SHAFER METHOD FOR DIAGNOSIS OF LUNG DISEASE SYMPTOMS - Tonni Limbong; Alex Rikki (INFOKUM, 2021)
Artificial intelligence is an effort to transfer intelligence that is added to a system that can be regulated in a scientific context or can be called artificial intelligence so that machines (computers) can do work as humans can do. Lung disease is a condition in which the lungs cannot function normally. Some of the most common include asthma, chronic obstructive pulmonary disease (COPD), pneumonia, tuberculosis, and lung cancer. The Dempster-Shafer method was first introduced by Dempster, who experimented with uncertainty models with a range of probabilities rather than a single probability. Application of the Dempster-Shafer method to diagnose lung disease, it can be concluded that inference techniques are easy to use in designing expert systems to get a conclusion but, it has weaknesses in finding these conclusions if the system has a large enough knowledge base and this will be very much use time and hinder the consultation process.